DOES SOCIAL MEDIA IMPROVE THE WELFARE OF TOURISM BUSINESSES? - Sasana, Hadi; Novitaningtyas, Ivo; Panjawa, Jihad Lukis (TRIKONOMIKA, 2020)
This research aims to analyze the factors that affect welfare of tourism business owners, especially the role of social media. This research uses primary data and cluster sampling method. Data was analyzed use multiple linear regression. The results show that social media has positive effect toward income of tourism business, but not significant. Moreover, income from tourism business has positive significant effect toward household consumption. Development of tourism gives benefits for local communities such as increase tourism business and increase their income. Therefore, tourism business should improve the ability of using social media as promotional tools to increase their welfare.